Memorable Tourism Experiences in Tourism: A Literature Review - Aprizal Haris Sinaga; Syafrizal Helmi Situmorang; Sembiring, Beby Karina Fawzeea (Jurnal Akutansi Manajemen Ekonomi Kewirausahaan (JAMEK), 2024)
Memorable tourism experiences have become a major focus in tourism research and service marketing in the modern era. This study presents a comprehensive literature review on the concept of memorable tourism experiences, determining factors, and their impact on tourist satisfaction and brand loyalty. By analyzing over 262 leading journal articles published between 2014 and 2023, this research maps the current research landscape and identifies trends and research gaps. The literature review results reveal key dimensions that shape memorable tourism experiences, including cognitive, affective, sensory, behavioral, and relational aspects. Determining factors such as the uniqueness of the experience, tourist engagement, authenticity, and service quality have been shown to have a significant influence on creating unforgettable experiences. Furthermore, this study explores the impact of memorable tourism experiences on tourist satisfaction, brand loyalty, and the intention to recommend. Theoretical and practical implications of these findings are discussed in depth, providing valuable insights for academics and tourism practitioners in designing, packaging, and marketing attractive and memorable tourism products and services.